2010
DOI: 10.1783/147118910791069475
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to diaphragm use: the views of advanced practice nurses

Abstract: Background and methodology Women have used the contraceptive diaphragm for decades. Although use has recently declined, the diaphragm may find a new role in STI/HIV and dual-prevention programmes when microbicides become available. We developed a questionnaire to examine seven provider issues identified as possible barriers to diaphragm use among advanced practice nurses (APNs) specialising in women's health. The perceived degree to which each issue represented a barrier was examined. Non-parametric correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Non-parametric correlation provides a single summary statistic (rho) that quantifies the strength of the association between a pair of variables. This is clearly useful when there are a number of factors under study (such as the seven potential barriers and four provider characteristics in Kulczycki et al's study) 1 and there is an interest in ascertaining/reporting the extent to which the provider characteristics are associated with barrier responses (28 associations in all). Furthermore, if there is a wish to draw inferences about the true strength of a correlation (rho), in the population from which the study sample was drawn, then the population estimate for rho can be reported with a confidence interval (CI), in accordance with good statistical practice.…”
mentioning
confidence: 99%
“…Non-parametric correlation provides a single summary statistic (rho) that quantifies the strength of the association between a pair of variables. This is clearly useful when there are a number of factors under study (such as the seven potential barriers and four provider characteristics in Kulczycki et al's study) 1 and there is an interest in ascertaining/reporting the extent to which the provider characteristics are associated with barrier responses (28 associations in all). Furthermore, if there is a wish to draw inferences about the true strength of a correlation (rho), in the population from which the study sample was drawn, then the population estimate for rho can be reported with a confidence interval (CI), in accordance with good statistical practice.…”
mentioning
confidence: 99%